Headache associated with moyamoya disease: a case story and literature review - Zach, Victor (Springer Milan, 2009)
Headache associated with moyamoya disease (HAMD) is common in moyamoya disease. However, the characteristics and classification of HAMD are largely unknown. We present a case of a 39-year-old woman with HAMD. To characterize and classify the features of this syndrome, the patient was asked to complete a 4-month diagnostic headache diary. There was a total of 15 ictal days. All episodes were without aura. The headache was more commonly pressing (10/15), mild to moderate in severity (14/15), unchanged by physical activity (11/15), and associated with photophobia (10/15). The International Headache Society Classification was utilized to determine that eight episodes met criteria for probable migraine without aura, while seven episodes met criteria for probable frequent episodic tension-type headache. We identified four other case reports of HAMD with partial descriptions of the characteristics. When combined with our patient, the median age was 34 years old (range 6–49, SD 16). Four were female, while the patient with cluster headache was male. The median time from headache onset to diagnosis with moyamoya disease was 9.5 months (range 0–192, SD 88.0). Headaches were described as migraine with aura in two of five cases, hemiplegic migraine in one of five, and cluster headache in one of five. The highest intensity was described as severe in three of three cases, in which headache intensity was reported. Meanwhile, nausea, vomiting, and photophobia were present in two of three cases, where these features were reported, while nausea without vomiting was seen in one of three cases. In all five cases, patients had other neurological symptoms, such as paresis, seizures, visual disturbances, dysarthria, allodynia, ptosis, and unilateral restless leg syndrome. In conclusion, HAMD can present as migraine without aura. It can be the first presenting symptom of moyamoya disease. The headache features are not diagnostic; hence, early neurovascular imaging should be considered in patients with new onset, refractory migraine-like headache, especially in the setting of other neurological symptoms to exclude underlying moyamoya disease. Further reports using headache diaries are needed to better characterize HAMD as well as to determine whether headache with tension-type features is also part of this condition.